Kaji Eksperimental Perambatan Pembakaran Pada Gambut (Smoldering Combustion Propagation Of Peat) Dari Gambut Tropis Kabupaten Pelalawan Pada Skala Laboratorium - Harun Orion; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A peat combustion in Indonesia is one of the biggest problems that support the increasing of the earth surface temperature by spreading of the CO2 gas in the air that significantly increased. Smoldering fire of peat has some of characteristics, which are slow burning, long-lasting combustion, and relatively low combustion temperatures. This method is done by examine the phenomenal that happens when the peat is burning down. In this matter, the peat from Pelalawan province of Riau that is going to be analyzed. The examination is going to use the peat that has been dried for 24 hours, and the moisture level after it has interacted with the air was 7.09%. The sample treatment prior to the combustion testing with the sample treatment without load and with loading, maximum temperature of peat burning 508.72 ° C and 500 ° C respectively, the rate of peat propagation of 5.17 cm/hour and 1.11 cm/hour. After testing the burning of smoldering peat, there was burned peat mass of 217 gram and 158 gram respectively.Kata Kunci : smoldering combustion, peat, combustion phenomenal